Mixed states in bipolar and major depressive disorders: systematic review and quality appraisal of guidelines. (13th May 2018) - Verdolini, N.; Hidalgo‐Mazzei, D.; Murru, A.; Pacchiarotti, I.; Samalin, L.; Young, A. H.; Vieta, E.; Carvalho, A. F.
Abstract : Objective: This systematic review provided a critical synthesis and a comprehensive overview of guidelines on the treatment of mixed states. Method: The MEDLINE/PubMed and EMBASE databases were systematically searched from inception to March 21st, 2018. International guidelines covering the treatment of mixed episodes, manic/hypomanic, or depressive episodes with mixed features were considered for inclusion. A methodological quality assessment was conducted with the Appraisal of Guidelines for Research and Evaluation‐AGREE II. Results: The final selection yielded six articles. Despite their heterogeneity, all guidelines agreed in interrupting an antidepressant monotherapy or adding mood‐stabilizing medications. Olanzapine seemed to have the best evidence for acute mixed hypo/manic/depressive states and maintenance treatment. Aripiprazole and paliperidone were possible alternatives for acute hypo/manic mixed states. Lurasidone and ziprasidone were useful in acute mixed depression. Valproate was recommended for the prevention of new mixed episodes while lithium and quetiapine in preventing affective episodes of all polarities. Clozapine and electroconvulsive therapy were effective in refractory mixed episodes. The AGREE II overall assessment rate ranged between 42% and 92%, indicating different quality level of included guidelines. Conclusion: The unmet needs for the mixed symptoms treatment were associated with diagnostic issues and limitations of previous research, particularly for maintenance treatment.